Perspective of dental professionals towards use of cast partial denture in Nepal - Sapkota, Srijana Mishra; Thakur, Smriti Narayan; Khanal, Bibek (Journal of Chitwan Medical College, 2022)
Background: With increase in treatment options for rehabilitation of partially edentulous patients, the use of cast partial denture in clinical practice as well as teaching curriculum has been decreased. The objective of this study was to evaluate the perspective of dental professionals towards use of cast partial denture in Nepal. Methods: The study consisted of nine close-ended questions regarding the use of cast partial denture by dental professionals in clinical practice throughout Nepal. The weblink of the questionnaire were shared via E-mail to dentists practicing in Nepal, to obtain a response of 350. Statistical analysis was done using SPSS version 26. Results: The study showed that the most preferred choice of rehabilitation was fixed partial denture by all dental professionals around 52.6% of , 60% of prosthodontists and 48.9% by other specialist dentists.The least preferred choice was Removable partial denture about 16.6% by general dental practitioners, 18.5% by prosthodontists and 13.3% by other specialist dentists.Among the different types of removable partial dentures, acrylic partial denture was the most preferred one and the primary reason for not recommending cast partial dentures by the dental professionals was too complicated procedure to be carried out. Nevertheless, majority of the dentists were in favor of giving more importance for teaching cast partial dentures in graduation curriculum. Conclusions: The study concluded that the use of cast partial denture is declining in clinical practice in Nepal due to the complicated procedure of fabrication and esthetic concern. Therefore, there is a need to emphasize the significance of teaching of cast partial dentures in graduation curriculum.